Rancang Bangun Sistem Conditioining Udara Berbasis IoT pada Studi Kasus Tanaman Selada Hidroponik - Anak Agung Angga Dwipa; I Gede Putu Wirarama Wedashwara W; Ariyan Zubaidi (Journal of Computer Science and Informatics Engineering (J-Cosine), 2020)
Air temperature and humidity as well as water temperature are very important environment variables in planting DFT hydroponic lettuce plants in a greenhouse. Controlling and monitoring the temperature and humidity generally still done manually by farmers. This problem can be solved by building an air conditioning system that implements the concept of the Internet of Things, which plays a role in automation control of actuators, and MQTT protocols as its data communication medium. Based on the test results, the system has been able to perform measurement and conditioning of air temperature and humidity, as well as water temperature in the greenhouse automatically. Comparison of observation and test result data with sunny weather conditions, showing that the average and maximum value of air and water temperature on test, lower compared to observation data. While the average and minimum value of humidity in the test are higher than the observation data.